Study of Three Level Cascade System: A Complete Analytical Approach (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
A density matrix based complete analytical solution for the probe transmission through a three-level cascade type Doppler free atomic system is obtained. The probe beam couples the ground level to the energy level lying at the middle whereas the control field is acting between the level at the middle and the upper most energy level. The analysis is valid for comparable values of probe and control Rabi frequencies too. The probe response shows EIT window when Raman condition is satisfied. The variation of the EIT width with control Rabi frequency under Doppler free condition is studied using the parameters of \(5S_{1/2}→ 5P_{3/2}→ 5D_{5/2}\) transitions of \(^{87}\)Rb. At high value of the probe field intensity compared to that of the control field, enhancement in probe absorption is noticed. The increase of the EIT width with control Rabi frequency under Doppler free situation is examined.